2007
DOI: 10.1598/jaal.50.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Tagging as a Social Literacy Practice

Abstract: Abstract. In this paper we introduce and describe the phenomenon of videogame street art as a specific kind of street art. We consider its materiality and significance, and conceptualize it in the light of a double manifestation of play: the playful appropriation of the city by the artist and the fact that street art encapsulates the act of playing videogames in a visual form. Digital play spills out of our computer screens and occupies the urban space with the explicit intention of involving spectators, who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 16 publications
0
26
0
2
Order By: Relevance
“…The literacies that helped to construct them as cool were also about style, for example, the writing on shoes-which was much like tagging (MacGillivray & Curwen, 2007) or the inscription of "claimed" spaces. There literacy practices were about posturing, showing how cool they were-a kind of ritual performance that for decades has incubated in the posthumous underground of black male speech communities.…”
Section: Resultsmentioning
confidence: 99%
“…The literacies that helped to construct them as cool were also about style, for example, the writing on shoes-which was much like tagging (MacGillivray & Curwen, 2007) or the inscription of "claimed" spaces. There literacy practices were about posturing, showing how cool they were-a kind of ritual performance that for decades has incubated in the posthumous underground of black male speech communities.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in their studies of graffiti writing, both MacGillivray and Curwen (2007) and Weinstein (2002) explored how "tagging" allowed urban minority youths who were marginalized elsewhere (e.g., school) to signal affiliation, or disaffiliation, with other taggers, gain respect from peers, and perhaps acquire "positive self-image" (Weinstein, 2002, p. 33) as writers. In a study of affiliation based upon sexual identity, Vetter (2010) reported on an adolescent girl who positioned herself as an invested reader and writer when completing a multigenre research project that allowed her to engage her sexuality and ref lect upon what it means to be a lesbian in contemporary society.…”
Section: Role Of Voluntary Writing In Adolescents' Livesmentioning
confidence: 99%
“…Second, staff members were not aware of any book talk, schoolwork, or pleasure reading and writing by the older children and adults. It is clear that although family literacy activities may have not been traditional storybook reading or explicit public displays, they did exist and were often linked to the literacy social practices of connecting with others and claiming competence (also see Gonzalez, 2001;Heath, 1983;MacGillivray & Curwen, 2007;Taylor & Dorsey-Gaines, 1988). As these often occurred both within the private space of a family's room, as well as in the midst of the frequently frenetic life that comes with multiple mothers and young children cooking, cleaning, playing, fighting, and crying, literacy events often went unrecognized.…”
Section: Reflections: Literacy In Shelter Livingmentioning
confidence: 99%